John Mirk's Festial: orthodoxy, Lollardy, and the common people in fourteenth-century England - Ford, Judy Ann (D.S. Brewer, 2006)
'Marvellously perceptive and insightful'. FIONA SOMERSET, Duke University. Written with largely uneducated rural congregations in mind, John Mirk's Festial became the most popular vernacular sermon collection of late-medieval England, yet until relatively recently it has been neglected by scholars -- despite the fact that the question of popular access to the Bible, undoubtedly regarded as the preserve of learned culture, along with the related issue of the relative authority of written text and tradition, is at the heart of both late-medieval heresy and the resultant reformulation of orthodoxy. It offers, in fact, an unparalleled opportunity to analyze the religious ideology communicated by the orthodox church to the vast majority of people in fourteenth-century England: the ordinary country folk. This book represents the first major examination of the Festial, looking in particular at the issues of popular culture and piety; the oral tradition; biblical and secular authority; and clerical power. JUDY ANN FORD is Associate Professor in the History Department of Texas A&M University-Commerce.